Productivity, Quality and Economics of Sweet Pepper (Capsicum annum) Cultivars under Modified Net House Conditions in Arid Regions: PRODUCTIVITY, QUALITY AND ECONOMICS OF SWEET PEPPER IN NET HOUSE - Choudhary, Santosh; Mamraj Meena; S. K. Moond; Dama Ram; U. N. Shukla (Annals of Arid Zone, 2024)
An experiment conducted during Rabi 2019-20 at the College of Agriculture, Jodhpur (Rajasthan), aimed to identify superior cultivars of sweet pepper (Capsicum annum L. Grossum Sendt.) with regards to yield, quality, and economic viability. The study included 20 sweet pepper cultivars and employed a randomized block design with three replications. Among the cultivars, ‘Pusa Deepti’ exhibited the tallest plant height (77.4 cm), highest number of leaves per plant (75.4), and greatest number of branches per plant (23.1) at 120 days after transplanting (DAT). Additionally, ‘Pusa Deepti’ also produced the longest fruits (9.73 cm) and highest number of fruits per plant (19.5), while ‘Orobelle’ displayed the widest fruit diameter (6.01 cm). The cultivar ‘Indra’ achieved 50% flowering in shortest duration of 68.0 days, while recording the maximum fruit weight (75.1 g), fruit yield plant-1 (1.34 kg), and fruit yield 1000 m-2 (4.88 tonnes). Conversely, ‘Orobelle’ exhibited the longest crop duration (221 days). In terms of quality attributes, ‘Arka Gaurav’ showcased the highest ascorbic acid content (169 mg 100 g-1) and total soluble solids content (7.5%), whereas ‘Indra’ displayed the longest shelf-life (8.6 days). Furthermore, ‘Indra’ demonstrated the highest net returns (Rs. 104666) and benefit-to-cost ratio (2.51) per 1000 m-2 area. The study underscores the importance of selecting appropriate cultivars of sweet pepper such as ‘Indra’ and ‘Pusa Deepti’ in western Rajasthan to avoid potential losses in sweet pepper cultivation with low yielding unsuitable cultivars.